Intrauterine contraceptive discontinuation reasons among female trial participants living with HIV in Cape Town, South Africa: A qualitative analysis - Subarna Pradhan; Elizabeth E. Tolley; Nontokozo Langwenya; Heidi E. Jones; Donald R. Hoover; Gregory Petro; Landon Myer; Catherine S. Todd (Frontiers Media S.A., 2023)
IntroductionWhile young women in South Africa may navigate both HIV infection and pregnancy risks, intrauterine contraceptive (IUC) use is low. Though IUCs have low failure rates, concerns exist about whether the IUC is an appropriate method choice for women living with HIV (WLHIV). In this qualitative study, we explore WLHIVs' experiences of using IUC and reasons for discontinuation.MethodsThis qualitative study included in-depth interviews (IDIs) with 17 WLHIV who electively discontinued their allocated IUC while participating in a randomized controlled trial comparing the safety of the levonorgestrel intrauterine system (LNG-IUS) and the copper intrauterine device (C-IUD) in Cape Town, South Africa. The transcripts were coded and emergent themes were grouped to examine women's experiences with IUC use and reasons for discontinuation, highlighting experiential differences between the two methods.ResultsWomen's experience with the allocated IUC related most commonly to bleeding and/or abdominal pain just after insertion. Most C-IUD discontinuers, but only one LNG-IUS discontinuer, complained of pain and/or increased bleeding as the main reason for removal. Three women (two LNG-IUS, one C-IUD) requested removal because they desired pregnancy, while two others discontinued due to fears the IUC was exacerbating non-gynecologic conditions (hypertension, diabetes). Generally, women acknowledged advantages of IUC use and many expressed their desire to continue use if not for the side effects.ConclusionsIn the South African context, IUC use for WLHIV should be promoted with specific counseling considerations. Both providers and potential users should receive specific information about potential menstrual-related side effects and countering common misperceptions to enable informed contraceptive decision-making.